Enhancing English Writing Skills: The Impact of the Task-Based Method at SMA Insan Cendekia Syech Yusuf - Akidah, Nur Faizah; Dollah, Syarifuddin; Iskandar, Iskandar; Noni, Nurdin; Sakkir, Geminastiti; Sunra, La (ELT Worldwide: Journal of English Language Teaching, 2025)
This research identifies the impacts of implementing the task-based method in teaching English writing at SMA Insan Cendekia Syech Yusuf. The study addresses a research question focusing on how implementing a task-based method in teaching English writing impacts students' writing skills. The study involved two English teachers and four SMA Insan Cendekia Syech Yusuf students. Data were collected through classroom observations, interviews with teachers and students, and written assignments. The findings reveal that the task-based method in teaching English writing is implemented through a structured task cycle involving pre-task, task, and post-task phases. Furthermore, the students reported positive impacts of task-based language teaching on their writing skills, particularly regarding organization, coherence, and critical thinking. However, the challenges related to language proficiency, task understanding, and time constraints were identified as barriers to full engagement. The emotional engagement varied among students, with some expressing frustration due to language limitations, while others thrived in the collaborative and problem-solving aspects of task-based language teaching. The study concludes that while the task-based method in teaching English writing shows significant potential for improving students' English writing skills, careful consideration must be given to task design, teacher support, and addressing student proficiency levels to maximize effectiveness. Future research should explore strategies for overcoming these challenges and enhancing student engagement in task-based language teaching in writing classes.